Addictions of youngsters living in the countryside: social and demographic background of alcohol consumption - Barabásné Kárpáti, Dóra (Acta Agraria Debreceniensis, 2014)
In the past 10–15 years, the consumption of illegal drugs has increased significantly both in Hungary and in our county. In parallel with the society’s getting more and more open, the fulfilment of personal freedom, and the spreading of globalisation and individual culture, the use of drugs has become more and more accessible and acceptable to the young. Social problems are supposedly connected with the interviewees’ alcohol consumption. The EuroADAD questionnaire was used. The sample covered 190 interviewees. I have processed the data with the SPSS statistical program package. The linear regression analysis was applied to examine the interrelations between the elements under study. Almost consume alcohol as well. Among the examined socio-demographic variables, youth alcohol consumption was most affected by the gender of the respondent, the dissatisfaction with living conditions, and the change of residence.